Initiation and growth of cavitation during the fatigue process of pre-oriented polypropylene film: In-situ SAXS study. (26th August 2020) - Chen, Zhenxian; Wang, Yingying; Xiong, Bijin; Zhu, Jintao
Abstract: Initiation and growth of cavitation during the fatigue process of pre-oriented polypropylene film have been studied via in-situ small angle X ray scattering (SAXS). The variation of the scattering invariant has been probed and the size of a single cavity has been fitted via a cylinder model. Two steps including initiation and growth of cavitation can be observed. In the first step, cavities initiate with a fast-growing rate at the beginning of the fatigue. The fitted length of a single cavity varies with the same frequency to the macroscopic stress, whereas the radius shows a higher frequency than the loading stress at the beginning of the fatigue process. In the second step, cavities stably grow after ca. 5 cycles. L and R deform in the same frequency with the macroscopic stress. Interestingly, the single cavity grows in the stretched direction and L enlarged with the loading stress, while in the lateral direction R decreases due to the lateral contraction. In this step, the volume of the cavity becomes stable cycle-by-cycle and the deformation of a single cavity is close to affine deformation due to the stable of the cavity. These findings could be of great importance for understanding the initiation and growth of pore during the fabrication of porous polypropylene membrane. Graphical abstract: Image 1 Highlights: Cavitation behavior during fatigue of PP were investigated via in-situ SAXS. Two steps including initiation and growth process were observed. Average size of cavities has been fitted during fatigue.